European patent system with special reference to patentability of pharmaceutical products and processes in the European Union and Turkey - Ortan, Rana (My University, 2005)
The purpose of this study is to examine various aspects of patentability and protection of inventions with special reference to pharmaceutical inventions both in the European Union and Turkey. A well-functioning patent system is crucial for sustainable development in all fields of industry. Especially, the pharmaceutical industry is a field which relies almost exclusively on patent protection. Effective protection and implementation of patent rights is essential to encourage investment in pharmaceutical research and development. In the first section of this study, a brief explanation about the general characteristics of intellectual property rights is given. Due to intensive and fragmented European intervention in the field of intellectual property rights; legislative E.C. harmonisation measures and international treaties in fields of copyright, trademarks, industrial designs, integrated circuits and geographical indications are mentioned. Principal patent related provisions of Paris Convention, Strasbourg Agreement Concerning the International Patent Classification and TRIPS Agreement are introduced. In the following part important characteristics of the European Patent Convention and the procedure for obtaining a European patent including post-grant opposition procedure and appeal procedure are scrutinized. Requirements for patentability in respect of European patents; that is, novelty, inventive step and industrial application are described in detail. There is a presentation of the functioning and the advantages of the Patent Cooperation Treaty System and the developments on establishing Community Patent. The time-consuming and expensive procedure for drug development and special cases concerning the patentability of pharmaceutical product and process inventions are also discussed in detail. In the last part, general aspects of Turkish patent legislation and patent protection with special reference to pharmaceutical inventions in Turkey are studied. Features that appeared for the first time in the field of patent protection in Turkish legislation after the enactment of the Decree Law No.551, are mentioned.

Bu çalışmanın amacı, özellikle Avrupa Birliği ve Türkiye'deki farmasötik buluşlarla ilgili olarak, buluşların patentlenebilirliğinin ve korunmasının çeşitli yönlerini incelemektir. İyi işleyen bir patent sistemi, sanayinin tüm alanlarında sürdürülebilir bir gelişme için çok önemlidir. Özellikle ilaç sanayinin büyük ölçüde patent korumasına bağlı bir alan olduğu söylenebilir. Farmasötik araştırma ve geliştirmeye yatırımı cesaretlendirmek için patent haklarının etkin korunması ve uygulanması asıldır. Bu çalışmanın birinci bölümünde , sınai mülkiyet haklarının genel nitelikleri hakkında kısa bir açıklama yer almaktadır. Sınai mülkiyet hakları alanındaki yoğun ve ayrıntılı Avrupa müdahalesinin varlığı nedeniyle; fikir ve sanat eserleri, markalar, endüstriyel tasarımlar, entegre devreler ve coğrafi işaretler hakkındaki Avrupa Topluluğu mevzuatı uyum tedbirlerinden ve uluslararası sözleşmelerden bahsedilmektedir. Paris Sözleşmesi, Milletlerarası Patent Sınıflandırmasıyla İlgili Strasburg Anlaşması ve TRIPS'teki patentlerle ilgili başlıca hükümler tanıtılmaktadır. Bir sonraki bölümde Avrupa Patent Sözleşmesinin önemli nitelikleri, ve ayrıca itiraz ve şikayet (temyiz) usullerini de içeren Avrupa patenti verilmesi usulü dikkatle incelenmektedir. Avrupa patentleri açısında patentlenebilirlik şartları; yenilik, buluş basamağı, sanayide uygulanabilirlik detaylı biçimde tanımlanmaktadır. Patent İşbirliği Anlaşmasının işleyişi, avantajları ve Topluluk patentine ilişkin gelişmelerden bahsedilmektedir. Zaman alan ve pahalı olan ilaç geliştirme prosedürü ve farmasötik ürün ve usul buluşlarının patentlenebilirliğine ilişkin özel durumlar detaylıca tartışılmaktadır. Son bölümde, Türk patent mevzuatının genel yönleri ve patent koruması üzerinde durulmakta, özellikle Türkiye'deki farmasötik buluşlar irdelenmektedir. 551 Sayılı Kanun Hükmünde Kararnamenin yürürlüğe girmesinde sonra Türk mevzuatında, patent koruması alanında ilk defa ortaya çıkan özelliklerden bahsedilmektedir
Keywords: Avrupa Birliği_Türkiye